2020
DOI: 10.3390/ijms21062115
|View full text |Cite
|
Sign up to set email alerts
|

Non-Photochemical Quenching Involved in the Regulation of Photosynthesis of Rice Leaves under High Nitrogen Conditions

Abstract: Excess and deficient nitrogen (N) inhibit photosynthesis in the leaves of rice plants, but the underlying mechanism is still unclear. N can improve the chlorophyll content and thus affect photon absorption, but the photosynthetic rate does not increase accordingly. To investigate this mechanism, three concentrations of N treatments were applied to two rice varieties, Zhefu802 and Fgl. The results indicated increased chlorophyll content of leaves with an increased N supply. Little discrepancy was detected in Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
4
2
0
Order By: Relevance
“…The ground sample results showed that the SPAD and Pn generally increased with nitrogen application (N1–N3 levels), then decreased at the N4 level, and finally recovered at the N5 level under the same leakage treatment at the jointing–booting stage, which also indicated that proper N application could improve the photosynthesis, while excessive N application not only had a poor effect on photosynthesis, but also affected plant growth and increased risk of contamination during leakage and drainage. This phenomenon was similar to that found by Cisse et al. (2020) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ground sample results showed that the SPAD and Pn generally increased with nitrogen application (N1–N3 levels), then decreased at the N4 level, and finally recovered at the N5 level under the same leakage treatment at the jointing–booting stage, which also indicated that proper N application could improve the photosynthesis, while excessive N application not only had a poor effect on photosynthesis, but also affected plant growth and increased risk of contamination during leakage and drainage. This phenomenon was similar to that found by Cisse et al. (2020) .…”
Section: Discussionsupporting
confidence: 92%
“…The ground sample results showed that the SPAD and Pn generally increased with nitrogen application (N1-N3 levels), then decreased at the N4 level, and finally recovered at the N5 level under the same leakage treatment at the jointing-booting stage, which also indicated that proper N application could improve the photosynthesis, while excessive N application not only had a poor effect on photosynthesis, but also affected plant growth and increased risk of contamination during leakage and drainage. This phenomenon was similar to that found by Cisse et al (2020). It might due to the fact that there was no significant difference in Rubisco activity and nonphotochemical quenching (NPQ) between the N4-N5 and the N3 level; thus, excessive energy could not be dissipated by NPQ, leading to oxidative stress, resulting in a decrease in Pn when excessive nitrogen was applied.…”
Section: Relationship Between Rice Growth and Canopy Multispectral Fe...supporting
confidence: 85%
“…A significantly higher Pn of 29.52 µmol (CO 2 ) m −2 s −1 at 150% of RDN was noted compared with a Pn of 17.41 µmol (CO 2 ) m −2 s −1 at 0% of RDN ( Devika et al., 2018 ). Flag leaf N content increased significantly with increased N application and is in accordance with the earlier findings ( Swarna et al., 2017 ; Cisse et al., 2020 ; Hou et al., 2020 ). Leaf N plays a crucial role in photosynthesis, which ultimately affects biomass production ( Ladha et al., 1998 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, plants exposed to long-term N deficiency would suffer an imbalance between the capability for absorbing light energy and consuming this excess light energy, resulting in the generation of reactive oxygen species (ROS) ( Yamori et al, 2016 ; Che et al, 2020 ; Mu and Chen, 2021 ). Photosystem II (PSII) is susceptible to HN and low N (LN) ( Cisse et al, 2020 ; Zhang Z. et al, 2021 ). HN and LN can inhibit either on the acceptor side or on the donor side of PSII, resulting in damaging PSII functions.…”
Section: Introductionmentioning
confidence: 99%
“…The donor side of PSII in Porphyridium cruentum , O. sativa , and Vitis labrusca were seriously impacted by N deficiency, leading to the inactivation of the oxygen-evolving complex (OEC) and the reduced photochemical efficiency ( Chen and Cheng, 2003 ; Zhao et al, 2017 ; Tantray et al, 2020 ). HN supply increases the PSII photoinhibition in O. sativa and Chenopodium quinoa because it does not sustain the balance of light absorption and utilization and consequently accumulates large amounts of H 2 O 2 at PSII ( Bascuñán-Godoy et al, 2018 ; Cisse et al, 2020 ). Diverse environmental stress can also result in the impairment of photosystem I (PSI) ( Ivanov et al, 2015 ; Lima-Melo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%